Visual attention modulates mu suppression during biological motion perception in autistic individuals - Sotoodeh, Mohammad Saber; Chien, Sarina Hui‐Lin; Hadjikhani, Nouchine (The European journal of neuroscience, 2024)
There has been a lot of controversy regarding mirror neuron function in autism spectrum disorder (ASD), in particular during the observation of biological motions (BM). Here, we directly explored the link between visual attention and brain activity in terms of mu suppression, by simultaneously recording eye‐tracking and EEGs during BM tasks. Nineteen autistic children (15 boys, mean age = 11.57 ± 4.28 years) and 19 age‐matched neurotypical (NT) children (15 boys, mean age = 11.68 ± 5.22 years) participated in the study. Each participant's eye movement and EEG were simultaneously recorded while watching four BM stimuli (walking, cartwheeling, free‐throwing and underarm throwing) and a scrambled condition. Mu (8–13 Hz) suppression index (SI) for central regions was calculated. Fixation counts and percent of fixation time were calculated as indices of eye movements. EEG results revealed significant mu suppressions in the central region in both groups for all BM actions. Eye‐tracking results showed that NT children had greater fixation counts and a higher percentage of fixation time than autistic children, indicating greater overall visual attention to BM. Notably, correlational analyses for both groups further revealed that individuals' fixation time and fixation counts were negatively correlated with the mu suppression index for all actions, indicating a strong association between visual attention and mu SI in the central region. Our findings suggest a critical role of visual attention in interpreting mu suppression during action perception in autism. This study directly explores the link between visual attention and mu suppression by simultaneously recording eye‐tracking and EEGs during BM tasks in autistic and NT children. Significant mu suppressions for BM in the central areas were observed in both groups. NT children had greater fixation time to BM than did autistic children. Notably, individuals' fixation time negatively correlated with mu suppression for BM, indicating a strong association between visual attention and mu suppression in the perception of action in autism.